Antiviral protein genetic markers physiologically induced in cucumber by beneficial microbes against cucumber mosaic virus - Allam Arafat Megahed; Badawy Abdelsalam Othman; Hassan Mohamed Mohamed Masoud; Mohamed Salah Eldin Helmy; Khaled Abdelfattah El-Dougdoug (Universitas Lampung, 2026)
Plant antiviral-induced protein markers provide important indicators of the effectiveness of plant defense responses against viral infection, supporting early detection, disease monitoring, and evaluation of antiviral strategies. In this study, various microbial biotic inducers were applied to cucumber plants to evaluate their ability to trigger systemic resistance against cucumber mosaic virus (CMV-EG). Biochemical and protein-profiling analyses were subsequently performed to quantify the induction of antiviral proteins and the activities of defense-related enzymes. In addition, bioinformatic, spectroscopic, and electrophoretic approaches were employed to characterize antiviral-induced proteins in cucumber plants treated with beneficial microbial isolates under CMV-EG infection. Among the tested treatments, Bacillus circulans produced the highest protein content, whereas B. subtilis resulted in the lowest protein accumulation relative to the healthy untreated control. SDS-PAGE analysis revealed a total of 45 newly induced antiviral protein markers across all microbial treatments, with molecular weights ranging from approximately 13 to 117 kDa and varying in number among the bacterial and fungal inducers. Peroxidase (POD) and polyphenol oxidase (PPO) activities also varied among the tested microbes, with several bacterial and fungal isolates markedly enhancing these defense-related enzymes. Furthermore, all treatments generated distinct POD and PPO isoenzyme patterns, collectively producing a wide range of newly induced antiviral protein markers that confirmed the strong elicitation potential of these biotic agents. Overall, the applied microbial isolates effectively activated antiviral defense responses in cucumber plants, inducing diverse proteins and enzyme markers that highlight their strong potential as biological resistance inducers against CMV-EG.